1981
DOI: 10.1111/j.1365-2125.1981.tb01112.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of zimelidine, a new antidepressant, on appetite and body weight.

Abstract: LETTERS TO THE EDITORS vivo only, whereas in vitro, it has no influence (Storstein, 1977). In order to rule out the possibility of an indirect effect of quinidine, occurring only in vivo, we compared the binding of digoxin in patients on long-term digoxin treatment with and without concomitant quinidine medication. The results (Table 2) indicate that the in vivo binding of digoxin did not differ between the two groups. It is concluded that serum protein binding of digoxin is not involved in the digoxin-quinidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The relationship between 5-HT re-uptake inhibition, food intake, and fluid consumption is complex (Gill and Amit 1989). While there are generally decreases in food intake (Gottfies 1981;Simpson et al 1981), fluid consumption (Gill and Amit 1989), and palatability (Leander 1987) post-treatment with an SSRI, motivational factors also appear to exert some control (Stellar and Stellar 1985). For instance, SSRIs not only enhance satiety (Blundell 1984) but selectively reduce preference for certain macronutrients (i.e., sweet items and carbohydrates) (Li and Anderson 1983;Wurtman 1977, 1979).…”
Section: Serotoninmentioning
confidence: 98%
“…The relationship between 5-HT re-uptake inhibition, food intake, and fluid consumption is complex (Gill and Amit 1989). While there are generally decreases in food intake (Gottfies 1981;Simpson et al 1981), fluid consumption (Gill and Amit 1989), and palatability (Leander 1987) post-treatment with an SSRI, motivational factors also appear to exert some control (Stellar and Stellar 1985). For instance, SSRIs not only enhance satiety (Blundell 1984) but selectively reduce preference for certain macronutrients (i.e., sweet items and carbohydrates) (Li and Anderson 1983;Wurtman 1977, 1979).…”
Section: Serotoninmentioning
confidence: 98%
“…SSRIs do suppress food intake [153,154] and fluid consumption [152] and decrease palatability [155]. Yet, motivational factors exert some control on the expression of these behaviors [156].…”
Section: Serotonin Reuptake Inhibitorsmentioning
confidence: 99%
“…Accordingly many agents that increase the availability of 5-hydroxytryptamine (5-HT) show anorectic activity (Nathan & Rolland, 1987;Wong & Fuller, 1987;Garattini et al, 1988;Samanin & Garattini 1990). They include several 5-HT uptake inhibitors which have proved effective in a number of experimental conditions of hyperphagia (see the above reviews) and some have also been reported to reduce body weight in man (Simpson et al, 1981;Smedegaard et al, 1981;Ferguson & Feighner 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly many agents that increase the availability of 5-hydroxytryptamine (5-HT) show anorectic activity (Nathan & Rolland, 1987;Wong & Fuller, 1987;Garattini et al, 1988;Samanin & Garattini 1990). They include several 5-HT uptake inhibitors which have proved effective in a number of experimental conditions of hyperphagia (see the above reviews) and some have also been reported to reduce body weight in man (Simpson et al, 1981;Smedegaard et al, 1981;Ferguson & Feighner 1987).Consistent with an inhibition of reuptake, 5-HT uptake blockers given acutely at pharmacologically effective doses generally rapidly lower the concentrations of 5-hydroxyindoleacetic acid (5-HIAA) in whole brain or selected brain areas of rats, without appreciably affecting the levels of its precursor 5-HT (Ross et al, 1981;Koe et al, 1983;Schmidt et al, 1988;Caccia et al, 1992a).Only fragmentary studies are available on the neurochemical effects of these drugs after repeated dosing in animals, which would allow a better assessment of the inhibition of amine uptake in relation to the therapeutic activity of the drugs. However, sertraline was reported to have no effect on 5-HIAA (and 5-HT) in selected rat brain areas after repeated administration, suggesting that its effect on 5-HT turnover is relatively short-lived (Leonard, 1988).…”
mentioning
confidence: 99%